The Discovery of the Koryaks and Their Perception of the World - Charrin, Anne-Victoire (ARCTIC, 1984)
The first information that we have about the Koryaks was reported in 1669 by Sosnovskij, the administrator of the small fortified town of Okhotsk, who had heard of them from the Tunguzian people. The first true ethnographic data were gathered only in 1700, when Atlasov (1935 [1891)], who had left the fortified town of Anadyr in 1697 to explore new territory, discovered Kamchatka and collected interesting information about the population of that peninsula, in particular the Koryaks. This was the beginning of a long period of exposure. Without doubt, it was the 'second Kamchatka expedition' (1733-1746) that supplied the most useful elements of the study for this region and its population. .